Formation of Social Care Character Through Social Studies Learning at SD Muhammadiyah 1 Bandung - Ayu Susanti , Rini (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This study explores the formation of social care character through Social Studies learning at SD Muhammadiyah 1 Bandung. Employing a qualitative approach, the research utilizes data collection techniques including interviews, observations, documentation, and questionnaires. Data analysis involves reduction, presentation, and conclusion drawing. Findings reveal that Social Studies learning significantly enhances students' social care character. This process involves integrating social care values into the Learning Implementation Plan (RPP) and applying these values through Direct Learning Practices (PPL). Social care character formation is achieved through both classroom instruction, where teachers provide explanations aligned with social care material, and practical activities. Students integrate these values into their daily routines, fostering a culture of social care at SD Muhammadiyah 1 Bandung.